THE IMPACT OF TRANSFER PRICING ON TAX AVOIDANCE MODERATED BY PROFITABILITY - Maheswari, Anandia Ayu; Reni Oktavia; Yenni Agustina (Universitas Airlangga, 2024)
This research aims to examine the impact of transfer pricing on tax avoidance with profitability acting as moderator. The independent variable examined in this study is transfer pricing, with leverage and profitabilitu serving as control variables. Tax avoidance is considered the independent variable, while profitability functions as the moderating variable. The study's population comprises mining companies listed in the Indonesian Stock Exchange between 2016 and 2018. The sampling was conducted using purposive sampling technique, resulting in 214 samples meeting the test criteria. Data analysis involves simple regression analysis and moderation regression analysis (MRA), employing the IBM SPSS Statistics software for analysis. The findings indicate that the transfer pricing variable does not significantly influence tax avoidance, and profitability weakens the relationship between transfer pricing and tax avoidance.